Wirksamkeit der Taktplanung aus Perspektive des Bauherrn am Beispiel von Produktionsimmobilien in der Automobilindustrie - Dlouhy, Janosch (Karlsruher Reihe Technologie und Management im Baubetrieb, 2022)
This work analyses the time effect that occurs due to the use of takt planning and takt control during the construction process from the perspective of the client. At first the historical courses of takt planning and takt control (TPTC) are aggregated. For an appropriate handling of the time reducing mechanisms three parameters are derived. The findings of this work are summarized into a recommendation for the use of takt planning for owners.